Market discounts and shareholder benefits: evidence from Australian REIT private placements. Issue 6 (19th August 2014) - Ratcliffe, Christopher; Dimovski, Bill; French, Nick
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose The purpose of this study is to examine the impacts of private placement announcements by Australian Real Estate Investment Trusts (A-REITs) on existing shareholders. The study examines 96 A-REIT private placements from January 2000 to December 2012. Design/methodology/approach Utilising event study methodology we examine the impact on existing shareholders wealth by measuring the abnormal returns around the placement announcement. We extend the analysis to model the A-REITs abnormal returns against a number of explanatory variables to investigate the possible drivers for the observed event study results. Findings Our results support the information signalling hypothesis, in that existing investors in A-REITs earn negative and significant cumulative abnormal returns of -1.3% over the three-day event window [-1, +1]. This result is in contrast to prior studies conducted on industrial firms, for example; Hertzel and Smith (1993), Krishnamurthy et al. (2005) and Wruck and Wu (2009). Practical implications Regression analysis shows A-REITs trading at a premium to net tangible assets and A-REITs that use placement funds for their core business have a positive impact on announcement abnormal returns. Originality/value This paper adds to the existing literature surrounding private placements and is the first paper, to the authors' knowledge, to examine the impact of Australian REITs.